FORMATION OF MODERN SKILLS BY ORGANIZING A ROLE-PLAYING GAME IN READING LITERACY CLASSES - Ataeva Bakhrinisa Abduvakhidovna (Web of Journals Publishing, 2024)
This article focuses on ways to engage students in collaboration, communication, critical and creative thinking through the use of role-playing in literacy instruction.
Keywords: elementary school, reading skills, role play, 4K model - critical, creative thinking, collaboration and communication.